Nonlinear effect of tuned mass damper system - Zhao, Bing. (2009)
On May 12, 2008, an 8.0-Magnitude earthquake struck Sichuan Province of China, and it was the most damaging earthquake for China since the 1976 Tangshan disaster. It has once again urged the importance of considering earthquake stability, especially when the structure in question is a human habitation. In building design, the structure must be able to survive under certain level of earthquake damage or withstand certain amount of time for escape. Enhancing structural functionality and safety against natural and manmade hazards is the motivation for civil engineers to develop new means and technologies. In recent years, considerable attention has been drawn towards research and development of structural control. Structural control strategies can be classified into three categories: passive, active, and semi-active control. Passive strategies are relatively well understood and widely accepted by the engineering community as a means for mitigating the damages from unfavorable dynamic loads. Tuned mass damper (TMD) systems are widely used passive vibration damping treatment. They are viscously damped 2nd order systems appended to vibrating structures. Proper selection of the parameters of these appendages, tunes the TMD to one of the natural frequencies of the under-damped flexible structure, resulting in the addition of damping to that resonance. This project aims to achieve a better understanding of TMD systems under earthquake conditions. In the course of this project, numerical analysis was performed base on lumped structure and soil system, and actual historical data of EI-Centro and Osaka Kobe earthquakes was used as input excitations. In order to simulate the deformations of structural elements under nonlinear condition, material nonlinearity was taken into account by introducing variable stiffness. In this report, it was found that the performance of TMD system in reducing structural responses was determined by the combination of structure, soil, and earthquake characteristics. Therefore, a new approach was introduced to integrate all the factors into the design stage of TMD parameters. From the nonlinear simulation, it was discovered that some structural elements experienced plastic deformations, and it was more serious at the lower part of the building. Furthermore, even with TMD installed, the final responses under nonlinear analysis were still almost twice of those without considering material nonlinearity. It was found that when nonlinear behavior occurred, the natural frequency of the structure-soil system shifted largely due to the change in stiffness of structural elements. Hence, the effectiveness of TMD system was depressed. However, the installation of TMD still largely reduced the responses compare to the condition without TMD.